2020
DOI: 10.1177/2041731420905701
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell-derived enteric neural crest cells repopulate human aganglionic tissue-engineered intestine to form key components of the enteric nervous system

Abstract: Models for enteric neuropathies, in which intestinal nerves are absent or injured, are required to evaluate possible cell therapies. However, existing options, including transgenic mice, are variable and fragile. Here immunocompromised mice were implanted with human pluripotent stem cell–derived tissue-engineered small intestine 10 weeks prior to a second survival surgery in which enteric nervous system precursor cells, or saline controls, were injected into the human intestinal organoid–derived tissue-enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…To further advance this concept, the precursors of all three germ layers have been combined to form stomach and esophageal organoids with an innervated smooth muscle layer [ 251 ]. Alternatively, engineered scaffolds are populated by primary or PSC-derived cells to create innervated mini-intestines [ 252 , 253 , 254 ]. Outside of the digestive system, sensorimotor organoids with functional neuronal components have been created from neuromuscular progenitors [ 255 , 256 ] or in a gastruloid approach to study the developmental process [ 257 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further advance this concept, the precursors of all three germ layers have been combined to form stomach and esophageal organoids with an innervated smooth muscle layer [ 251 ]. Alternatively, engineered scaffolds are populated by primary or PSC-derived cells to create innervated mini-intestines [ 252 , 253 , 254 ]. Outside of the digestive system, sensorimotor organoids with functional neuronal components have been created from neuromuscular progenitors [ 255 , 256 ] or in a gastruloid approach to study the developmental process [ 257 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Almost all prior studies, including ours, utilize male mice as the host for tHIO in vivo growth. 3,4,[7][8][9][10][11][12] One likely factor contributing to this discrepancy is that male mice are larger and therefore have larger kidney size F I G U R E 2 Epithelial barrier function is not altered in transplanted human intestinal organoids (tHIOs) from male and female hosts. Transepithelial electrical resistance and short circuit current are not significantly different in tHIOs from male (n = 4) vs. female (n = 5) hosts (A,B).…”
Section: Discussionmentioning
confidence: 99%
“…An additional area lacking in the present HIO literature is the exploration of murine host sex as a biological variable (SABV) in tHIO development and function. The majority of tHIO publications report utilizing only male murine hosts or simply do not report host sex 3,4,7–12 . Only one previous study reported growing tHIOs in both male and female mice, but sex‐related differences were not described 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Current advancements have extended into biomanufacturing MSCs for major expansion in therapeutic use under good manufacturing practices that utilizes assays to ensure the efficacy and quality safety of MSCs [ 85 88 ]. Induced pluripotent stem cells (IPSCs) have been utilized to derive enteric neural crest cells resulting in proliferative migratory neuronal and glial cells of damaged intestine tissue [ 89 ]. Other sources to target ENS include embryonic stem cells [ 90 , 91 ], which can differentiate into neural crest cells, neural precursors, and neurons [ 92 95 ].…”
Section: Current Approaches To Gi Bioengineeringmentioning
confidence: 99%